Analysis of the Potential Attractiveness of Business Investment Cooperation in Natural Resources and Cultural Development of Fakfak Regency: (Ethics, Integrity, Elegance, & Innovation Viewpoint of Business Actors) - Irfan Hasim; Pompong Budi Setiadi; Rifdah Fitrianti (Research Trend in Technology and Management, 2023)
The Fakfak Regency Government still has problems in terms of ethics, integrity, elegance and innovation of business actors, this is urgently needed in business development to increase the potential attractiveness of business investment cooperation so that it can run well so that it can increase regional income. The research was carried out during May – December 2023. Descriptive research method with a combination approach of quantitative analysis. Data was obtained through a direct survey of respondents who had been deliberately determined. The data obtained are given a weight value based on the assessment indicators obtained from the results of the preliminary research. The results of the study are presented in the form of Correlations, f-Test, t-Test and regression equation model obtained from the spss statistical device version 2.3.